Basic combinatorial configurations in preschool teacher education - Živanović Milan V.; Pikula Milenko T. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2013)
The paper presents arguments for the need for combinatorial education of preschool teachers. To this effect, the author presents the minimal content which such training should cover in his opinion. Through examples related to practical situations, the author seeks to bring this matter closer to the readers who have had difficulties concerning mathematics during school.